PRESENTATION OF PULMONARY TUBERCULOSIS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Aziz, Rizwan; Khan, Abdur Rab; Qayum, Iftikhar; Mannan, Modood ul; Khan, M Tariq; Khan, Nisar (Journal of Ayub Medical College Abbottabad, 2002)
Background: Pulmonary tuberculosis (PTB) may be easily confused with other chest diseases during its initial presentation. This study was carried out to identify presenting clinical and laboratory features that differentiate PTB from other diseases and to correlate clinical features and laboratory findings. Methods: This study was carried out at the Department of Pulmonology, Ayub Teaching Hospital Abbottabad, from September 1999 to December 2000. A total of 46 patients were included in the study after being clinically diagnosed as pulmonary tuberculosis. These patients were subjected to detailed history taking recording age, sex, weight, socioeconomic status and smoking habits. They were clinically evaluated and laboratory tests including Hemoglobin, ESR, TLC, DLC and sputum for AFB were done. They were put on standard anti-tuberculous therapy and followed from 2 to 5 months to monitor treatment effect. Statistical analysis was performed by SPSS 8 computer program. Results: A bimodal presentation (below age 30 years and above age 50 years), fever, productive cough, weight loss, night sweats and raised ESR were the most common findings in PTB patients. Sputum AFB smears were positive in 50% of diagnosed cases. No correlation was found between clinical and laboratory parameters in establishing a confident diagnosis of the disease. Conclusions: The study highlights the importance of further research to pinpoint stronger and more reliable criteria for diagnosis.